The Influence of Competence, Work Environment and Industrial Internships on Learning Effectiveness Through Teacher Performance in Vocational High Schools - Savitri, Wici Aan; Maksum, Hasan; Irfan, Dedy; Indrawan, Eko (STKIP Singkawang, 2025)
This study aims to analyze the influence of competence, work environment, and industrial internship on learning effectiveness through teacher performance in Vocational High Schools (SMK) using a Systematic Literature Review (SLR) approach. A total of 35 relevant articles published between 2020 and 2025 were thematically analyzed to identify patterns and gaps in related research. The study results show that teacher competencies, especially in pedagogical and professional aspects, strongly influence student motivation and learning outcomes. A conducive working environment and effective leadership also improve teachers' performance in delivering materials optimally. In addition, the industrial apprenticeship program (PKL) for students and teachers is proven to improve the relevance of learning to the needs of the world of work, although its implementation still faces various challenges such as the lack of guidance from the industry and the mismatch of tasks with student competencies. This review suggests the need for continuous synergy between schools and industry and strengthening teacher training to make vocational education more responsive to labor market dynamics. Further research is recommended to examine the long-term impact of vocational education on graduates' career success and the development of effective school-industry partnership models